Taking Evil Seriously - Pihlström, S. author. aut Link
VIII, 139 p.
Keywords: While moral philosophy has traditionally been understood as an examination of the good life, this book argues that ethical inquiry should, rather, begin from an examination of evil and other 'negative' moral concepts, such as guilt and suffering.